The Impact of the Pandemic on the Elimination of Indie Music Performers - Mulyadi Cahyoraharjo; rubby Sanjaya (Cinematology: Journal Anthology of Film and Television Studies, 2022)
The COVID-19 pandemi has had a devastating impact on every sector of the economy, especially on indie musik players. Indie musik players feel the many rights that have been changed when covid-19 emerged in Indonesia. The most noticeable influence on indie musik players is their income because, during the pandemi, many things limit movement. Meanwhile, indie musikians earn income from playing from stage to stage which requires a large audience. The Indonesian government during the pandemi in the last 1 year has continued to aggressively limit indoor and outdoor gatherings, while indie musikians need this crowd to establish relationships with connoisseurs or fellow indie musikians. In collecting data, this study used an online survey by filling out a questionnaire. The results of the study tested how far the pandemi has impacted the income of indie music players.